Evaluasi pelaksanaan road map penataan angkutan umum di Denpasar, Badung, Gianyar dan Tabanan (studi kasus angkutan umum trans sarbagita) - Kubontubuhi, Ekapria Dharana; AA.Gde Sutrisna WP (Journal of Placemaking and Streetscape Design, 2023)
This study aimed to evaluate three aspects of Trans Sarbagita Public Transport Improvement Program consisting of the implementation of the Road Map, analysis of the factors that became the main obstacle and evaluation of the effectiveness of the programs which had been underway. The study used qualitative method with a descriptive pattern through interviews, observation and documentation of institutional factors, stages of the operation of the route, provision of means of transport / bus, provision of operation supporting facilities, financing the purchase of services, passenger fares and service quality. The results showed that the provisions of institutional facilities and institutional forms had not been fulfilled; the number of route network was not in accordance with the plan, the lack of the number of buses, bus stops and traffic signs, limited service fees and low passenger fares and service quality. Therefore a cooperation agreement should be made and the establishment of institutions engaged in service for the management, rearranging the lane routes, increasing the number of buses, bus stops and signs as needed, preparing and evaluating the suitability of bus fares and improving service quality.